Ice-sheet-driven methane storage and release in the Arctic - Portnov, Aleksei D; Vadakkepuliyambatta, Sunil; Mienert, Jurgen; Hubbard, Alun Lloyd (Nature Communications, 2016)
Published version. Source at http://dx.doi.org/10.1038/ncomms10314 A manuscript version of this article is part of Aleksei Portnov's Ph.D. thesis, which is available in Munin at http://hdl.handle.net/10037/8220 It is established that late-twentieth and twenty-ﬁrst century ocean warming has forced dissociation of gas hydrates with concomitant seabed methane release. However, recent dating of methane expulsion sites suggests that gas release has been ongoing over many millennia. Here we synthesize observations of B1,900 ﬂuid escape features—pockmarks and active gas ﬂares—across a previously glaciated Arctic margin with ice-sheet thermomechanical and gas hydrate stability zone modelling. Our results indicate that even under conservative estimates of ice thickness with temperate subglacial conditions, a 500-m thick gas hydrate stability zone—which could serve as a methane sink—existed beneath the ice sheet. Moreover, we reveal that in water depths 150–520 m methane release also per- sisted through a 20-km-wide window between the subsea and subglacial gas hydrate stability zone. This window expanded in response to post-glacial climate warming and deglaciation thereby opening the Arctic shelf for methane release.